(untitled) (Revista de Crítica Literaria Latinoamericana, 2017)
This study analyzes the relationship between literature and politics in the work of Rodolfo Walsh (1927-1977), as well as the tensions resulting from the convergence of these markedly opposed spheres. Focusing on two stories, “Fotos” (1965) and “Un oscuro día de justicia” (1967), I reflect on the way in which the imaginary is integrated within the political without compromising its aesthetic value. Toward this end, I in turn, devote significant attention to the definition and the reappraisal of the image both in fictional and testimonial literature. Manifest in these two corpuses, I argue, is a critical response to the realism that commonly accompanies revolutionary commitment.